The Effect Of Mentoring By Involving Pkk Mothers On Weight Control Of Pregnant Women - Mayang Citra Hariati; Krisdamayanti Harefa (Fakultas Kebidanan Institut Kesehatan Medistra Lubuk Pakam, 2023)
Mentoring to pregnant women is a form of community participation carried out with the aim of improving the degree of maternal and fetal health during pregnancy. One of the efforts made to reduce maternal mortality is to maximize antenatal care (ANC) services by involving companions to motivate pregnant women to check their pregnancies at health facilities regularly in each trimester. Midwives assess weight gain in mothers during pregnancy, insufficient weight gain during pregnancy can result in chronic energy deficiency (KEK) and potential complications in childbirth such as bleeding and low birth weight babies (BBLR), while excess weight gain can cause obesity which has an impact on pregnancy with preeclampsia and macrosomia in the fetus. To check the pregnancy so that the assessment and monitoring of the health condition of the mother and fetus is more optimal. This can increase morbidity and mortality for mothers and babies who will be born later. This study is a Quasy Experimental study, with a total sample of 28 pregnant women, which was divided into two groups, namely the intervention group and the control group, which was illustrated in the form of a table using the Wilcoxon test to see the influence before and after the intervention was given, then obtained a p-value of 0.025 <0.05. The results of this study show that there is an influence of mentoring PKK mothers on the weight of pregnant women in Denai Bird's Nest Village, Pantai Labu. So it is hoped that PKK mothers can increase cooperation with health workers and can motivate and provide education to pregnant women to check their pregnancies so that the assessment and monitoring of maternal and fetal health conditions is more optimal.